Efektivitas Permainan Roda Putar terhadap Pengetahuan dan Sikap Siswa Mengenai COVID-19 di SD Cahaya Pengharapan Abadi Deli Serdang - Simanjuntak, Gamalielya Gera; Andayani, Lita Sri (UI Scholars Hub, 2022)
Background. In 2020 the world experienced a COVID-19 pandemic that required educational institutions, namely schools to be closed, as a result of which 157,166 students dropped out, including 59,443 elementary school students. WHO suggested that schools reopen with strict health protocols, but many elementary school students still do not comply with health protocols. Objective. Knowing the effectiveness of the spinning wheel game on students' knowledge and attitudes about COVID-19 at Cahaya Pengharapan Abadi Elementary School, Deli Serdang. Method. Using the Pre-Experimental Design research design with the One Group Pretest-Postest method. The population of students in class V at Cahaya Pengharapan Abadi Elementary School, Deli Serdang, was 42 students. The sample used 15 students using proportional sampling as a technique. The data collection used a questionnaire. Results. The result score average for knowledge was 18.87 (p = 0.001) and attitude 19.27 (p = 0.001). Conclusion. The rotary wheel game proved effective in improving the knowledge and attitude of elementary school students.